Christianity and the Holocaust of Hungarian Jewry - Herczl, Moshe Y. (NYU Press, 1993)
The complicity of the Hungarian Christian church in the mass extermination of Hungarian Jews by the Nazis is a largely forgotten episode in the history of the Holocaust. Using previously unknown correspondence and other primary source materials, Moshe Y. Herczl recreates the church's actions and its disposition toward Hungarian Jewry. Herczl provides a scathing indictment of the church's lack of compassion toward and even active persecution of Hungary's Jews during World War II.